Optimal control of paralympic wheelchair curling - Laschowski, B.; Mehrabi, N.; McPhee, J. (19th Biennial Meeting of the Canadian Society for Biomechanics, 2016)
Scientists have proposed that the human central nervous system resolves kinematic redundancies during multibody movements using optimal control theory [1]. An emerging area of human movement science involves the biomechanics and motor control of athletes with physical disabilities. To the best of the authors` knowledge, there has been no research published regarding the motor control of Paralympic athletes. The objectives of this research were: i) develop a novel multibody biomechanical model of a Paralympic athlete with a spinal cord injury (SCI), and ii) compare the simulated joint kinematics from different optimal control objective functions with those experimentally measured during an arbitrary sport movement (i.e., wheelchair curling) in the interests of quantifying the motor control employed by the Paralympic athlete.